External validation of Standardized KELIM and platinum-resistant recurrence scores in patients with advanced epithelial ovarian cancer - Nina Oufkir; Roman Rouzier; Xavier Paoletti; Claire Bonneau (BMC, 2024)
Abstract Background Neoadjuvant chemotherapy followed by interval debulking surgery is currently a common treatment option for advanced epithelial ovarian cancer (EOC). The Standardized CA-125 ELIMination rate constant K (Std KELIM) and the Platinum Resistant Recurrence (PtRR) Score have been proposed as markers of tumor chemosensitivity. The aim of our study was to validate these tools for predicting platinum sensitivity in a real-world population of patients with advanced EOC treated with neoadjuvant chemotherapy. Experimental design All patients with advanced EOC treated with neoadjuvant chemotherapy at the Institut Curie between 2000 and 2015 were included. The Std KELIM was calculated with the CA-125 concentrations during the first 100 days of chemotherapy. The predictive value of Std KELIM and PtRR scores for the risk of subsequent PtRR was assessed using receiver operating characteristic (ROC) curve analysis, logistic regression and calibration curve. Kaplan-Meier survival analysis was performed for the treatment-free interval from platinum (TFIp) therapy and overall survival (OS). Results Std KELIM data were available for 149 patients. The AUC was 0.67 for PtRR. A low Std KELIM was significantly associated with PtRR (OR = 0.19 (95% CI [0.06, 0.53], p = 0.002)) according to the univariate analysis. The calibration curve of the PtRR showed a slight but significant underestimation (p = 0.02) of the probability of platinum resistance. Favorable Std KELIM (≥ 1) alone and combined with the completeness of surgery were associated with significantly better survival in terms of TFIp and OS. Conclusions Std KELIM is an early prognostic marker of chemosensitivity in a real-life setting complementary to surgical status. It could help the clinician in the early management of patients by identifying those with a worse prognosis.